Eksplorasi, Identifikasi dan Studi Fenologi Pembungaan dan Pembuahan Kultivar Salak di Kecamatan Bebandem, Karangasem, Bali - Siregar, Faisal; Rai, I Nyoman; Wiraatmaja, I Wayan (Nandur, 2021)
Exploration, Identification and Study of Flowering and Fertilization Phenology of Salak Cultivars in Bebandem District, Karangasem, Bali. Salak in Bali is one of the most popular fruit plants and widely developed in Bali. This study aimed to identify the types of zalacca cultivars in Karangasem Regency, compiled the profile of plant genetic resources concerning morphological and agronomic characters, photographs of genetic resources as well as the flowering and fruiting phenology of salak cultivars. The research was conducted in Bebandem District, Karangasem Regency, from December 2019 - April 2020. The research was consisted of 5 (five) stages, i.e .: (1) collected secondary data, (2) collected primary data, (3) identification the morphology and agronomy characters, (4) phenology studies of flowering and fertilization and (5) tabulation and data analysis. The results showed that there were 12 types of salak cultivars in Bebandem District, with different phenology of flowering and fertilization for each cultivar. Based on the agronomic characters, the most superior salak cultivated include salak gula pasir (Salacca zalacca var Gula Pasir), salak gondok (Salacca zalacca var Gondok) and salak nangka (Salacca zalacca var Nangka).